(untitled) (Physical Culture and Sport: Scientific Perspective, 2025)
The article presents the results of a study on the functional state of the cardiovascular system in higher education students who regularly engage in physical activity. The aim of the study was to examine adaptive changes in cardiovascular function by assessing basic physiological parameters (heart rate and blood pressure) and an integrated index – the cardiovascular efficiency coefficient (CEC). The study sample included 48 first-year male students aged 17-19 from Khmelnytskyi National University, who combine academic workloads with regular sports training and lead an active lifestyle. The research was conducted under resting conditions using standard techniques for measuring heart rate (HR) and blood pressure (BP), followed by the calculation of CEC. The results were processed using methods of mathematical statistics: mean values and standard deviations were calculated, and CEC values were classified according to functional efficiency levels. The analysis showed that average values remained within physiological norms: HR – 74.2 ± 9.5 bpm, systolic BP – 118,2 ± 10,5 mmHg, diastolic BP – 62,1 ± 6,7 mmHg, and CEC – 8,89 ± 1,55. CEC distribution revealed that 31,3 % of students demonstrated high cardiovascular efficiency (CEC < 8,0), 45.8 % fell within the normal range (8,0–10,0), and 22,9 % showed elevated CEC values (>10,0), which may indicate physical strain, emotional stress, or individual peculiarities in adaptation. The findings confirm the feasibility of using CEC as a simple, accessible, and sensitive indicator for monitoring the functional condition of the cardiovascular system in physically active youth. The results can serve as a foundation for personalized recommendations regarding physical loads in both academic and sports settings. Further research is warranted to monitor CEC dynamics throughout the training cycle and to integrate this index with other physiological markers for a comprehensive assessment of cardiovascular adaptation.